Diving Deeper - Halpin, Terry; Rugaber, Spencer (Taylor & Francis Group, 2015)
This chapter builds on the concepts and syntax of the LogiQL language considered in the previous chapters, introducing some more advanced features of the language and describing how programs are executed by the LogiQL engine. The first unit discusses aggregation functions for computing minima and maxima. We then identify some safety conditions to ensure that rules and queries execute in a finite time. After this, a description is given of how derivation rules are processed. Then come two units relating to the handling of changes to the EDB. The first examines how delta rules and pulse predicates may be used to make changes to the database, and the second provides a simple explanation of how transactions are supported in LogiQL. The final unit considers some further built-in operators and functions (scalar or aggregation) that can be useful. The consolidation exercise at the end gives you an opportunity to test your mastering of the new concepts and syntax considered in the chapter.